Cancer and heart disease: associations and relations - de Boer, Rudolf A. (Eur J Heart Fail, 2019)
Emerging evidence supports that cancer incidence is increased in patients with cardiovascular (CV) disease and heart failure (HF), and patients with HF frequently die from cancer. Recently, data have been generated showing that circulating factors in relation to HF promote tumour growth and development in murine models, providing proof that a causal relationship exists between both diseases. Several common pathophysiological mechanisms linking HF to cancer exist, and include inflammation, neuro‐hormonal activation, oxidative stress and a dysfunctional immune system. These shared mechanisms, in combination with risk factors, in concert may explain why patients with HF are prone to develop cancer. Investigating the new insights linking HF with cancer is rapidly becoming an exciting new field of research, and we herein review the most recent data. Besides insights in mechanisms, we call for clinical awareness, that is essential to optimize treatment strategies of patients having developed cancer with a history of HF. Finally, ongoing and future trials should strive for comprehensive phenotyping of both CV and cancer end points, to allow optimal usefulness of data, and to better describe and understand common characteristics of these two lethal diseases.